ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN GIZI BURUK PADA BALITA DI KABUPATEN KEBUMEN TAHUN 2010 - Hidayati, yuliana; ., Asrin; ., Sumarni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
Malnutrition is the nutrition problem and one of the factor that encourage the baby mortality and children in Indonesia. There are some of the factors that affect the malnutrition incidence for the baby like income, knowledge, infection disease, health facility usage, food intake, food supply in family, children caring, education and environment health. To find out the factors that affect the malnutrition incidence for the baby in Regency of Kebumen. This research method is analysis descriptive with the Cross Sectional approach. Samples in this research are 60 people respondents where 30 people who have the malnutrition children and 30 people have the children with good nutrition this research uses the primary and secondary data by using Deskriptive, Chi-Square and Logistic Regression analytic. The income of mother at least is insufficient that are 34 people (56.7%). Knowledge of mother about the baby nutrition is low that is 40 people (66.7%), 23 baby (38.3%) have infection and 49 people (81.7%) uses the health facility with not good. There is significant correlation between the income Ï = 0.009, knowledge Ï = 0.003, infection disease in the baby Ï = 0.017 and health facility usage Ï = 0.020 with malnutrition incidence in the baby is the knowledge (OR=4.701). The factors that affect the malnutrition incidence for the baby in Regency of Kebumen is income, knowledge, infection diseases and utilization of health facilities and the most significant correlation is knowledge. It would be better for the mother of baby to concern for the health condition and necessity of their children nutrition. KeywordsÂ Â Â Â Â Â  : Malnutrition, Baby